Random Error Estimation and Propagation Analysis for Satellites’ Initial Positions - Huanqin Wu; Maocai Wang; Zhiming Song; Xiaoyu Chen; Guangming Dai (International Journal of Aerospace Engineering)
An increasing number of satellites are currently being launched into orbit to work in the form of clusters or constellations. However, the initial orbit position is accompanied by random errors, which will propagate during their running. Therefore, the orbit precision of the satellites directly affects space safety, network accuracy, and operating efficiency. Hence, accurate and fast random error estimation is essential to improve satellite control. The traditional method will take much time and cost, and it is associated with complex calculations or low accuracy, especially for large-scale constellations. In this paper, a random error evaluation model based on the ellipsoid is proposed. It can be used to estimate initial positions and error propagation for any orbit satellites. By comparing with the experiment results using the Monte Carlo method, it is proved that the proposed model is relatively simple, highly effective, and good at accuracy.